From warfare to welfare : defense intellectuals and urban problems in cold war America - Light, Jennifer S (Johns Hopkins University Press, 2003)
During the early decades of the Cold War, large-scale investments in American defense and aerospace research and development spawned a variety of problem-solving techniques, technologies, and institutions. From systems analysis to reconnaissance satellites to think tanks, these innovations did not remain exclusive accessories of the defense establishment. Instead, they readily found civilian applications in both the private and public sector. City planning and management were no exception. Jennifer Light argues that the technologies and values of the Cold War fundamentally shaped the history of postwar urban America. From Warfare to Welfare documents how American intellectuals, city leaders, and the federal government chose to attack problems in the nation's cities by borrowing techniques and technologies first designed for military engagement with foreign enemies. Experiments in urban problem solving adapted the expertise of defense professionals to face new threats: urban chaos, blight, and social unrest. Tracing the transfer of innovations from military to city planning and management, Light reveals how a continuing source of inspiration for American city administrators lay in the nation's preparations for war.